(untitled) (Quest Journal of Management and Social Sciences, 2019)
Background: Concept of single women is not an issue of trauma psychologically and socio-economically in modern household and society, unlike in traditional and patriarchal society. However, it still is a big issue in Nepalese society as well as in academic discourse and development practices, although Nepalese polity is based on postmodernism and has been following western characters. Further, developmental approachesare a proactive gender balanced from top to bottom. Objectives: To examine the relationships between single women, vulnerability level and household structure in rural Nepali society. Methods:Primary data are collected from household survey by using descriptive statistics. Results: It finds the emergence and increment of single women due to the conflict in Nepal (1996-2006).Growing foreign employment led to divorces (1999-2019) and natural deaths of male population paving the way for multifaceted vulnerability of single women in nuclear and joint family. Conclusion:Despite the growth of financial and political independence of single women, vulnerability still is acute in Nepal. It is a barrier to single women’s happiness and empowerment. Implication:Findings of this study can be used by policy makers and concerned authorities to make decisions and take appropriate action.